Delegation and Rewards - Stefan Vetter (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2012)
We study experimentally whether anti-corruption policies with a focus on bribery might be insufficient to uncover more subtle ways of gaining an unfair advantage. In particular, we investigate whether an implicit agreement to exchange favors between a decision-maker and a lobbying party serves as a legal substitute for corruption. Due to the obvious lack of field data on these activities, the laboratory provides an excellent opportunity to study this question. We find that even the pure anticipation of future rewards from a lobbying party suffices to bias a decision-maker in favor of this party, even though it creates negative externalities to others. Although future rewards are not contractible, the benefitting party voluntarily compensates decision-makers for partisan choices. In this way, both receive higher payoffs, but aggregate welfare is lower than without a rewards channel. Thus, the outcome mirrors what might have been achieved via conventional bribing, while not being illegal.
urn:nbn:de:bvb:19-epub-12884-3
Keywords: C91; D62; D63; D73; K42; 330; delegation; gift exchange; corruption; lobbying; negative externalities; Kooperative Führung; Korruption; Interessenpolitik; Externer Effekt; Austauschtheorie (Soziologie); Test